Effects of omega-3 fatty acid supplementation on nutritional status and inflammatory response in patients with stage II-III NSCLC undergoing postoperative chemotherapy: a double-blind randomized controlled trial - Gui, Long; Cheng, Mingjin; Zheng, Min; Ning, Chengdong; Huo, Qianlun (Frontiers in Nutrition, 2023)
Background The primary objective of this study was to investigate the effects of oral omega-3 fatty acids in lowering the risk of malnutrition and improving the inflammatory response in patients with stage II-III lung cancer receiving postoperative chemotherapy. Methods 103 lung cancer patients identified as being at risk for malnutrition according to the 2002 nutritional risk screening criteria were randomized into either the omega-3 fatty acid supplementation group or the placebo group during postoperative chemotherapy. Data on anthropometric parameters, laboratory nutritional indicators, and inflammatory markers were collected, and changes and differences between the two groups were compared and analyzed. Results 63 patients were included in the final analysis. The baseline information of the two groups of patients was comparable (p>0.05). After 12 weeks, patients in the treatment group exhibited significantly higher levels of hemoglobin (11.26±1.25 vs.10.60±0.94, p=0.021) and serum albumin (45.38±5.06 vs.42.66±5.06, p=0.036) compared with those in the placebo group. Meanwhile, the levels of inflammatory factors C-reactive protein (2.16±1.06 vs. 4.11±1.72, p<0.001), interleukin-1 (6.61±2.19 vs.10.85±3.61, p<0.001), interleukin-6 (2.48±1.20 vs. 4.53±0.98, p<0.001), interleukin-8 (9.26±2.69 vs. 39.01±6.53, p<0.001), and tumor necrosis factor-α (1.88±0.60 vs. 4.07±0.97, p<0.001) were significantly decreased in the treatment group. In contrast, differences in weight, BMI, upper arm circumference, triceps skinfold thickness, triglycerides, cholesterol, and IFN-γ between the two groups were not statistically significant (p>0.05). Finally, in the treatment group, the levels of hemoglobin (10.89±1.15 vs. 11.82±1.21, p=0.042), triglyceride (0.92±0.29 vs. 1.03±0.22, p=0.043), and cholesterol (3.56±0.82 vs. 4.23±0.88, p=0.045) were higher in stage II patients after the intervention compared with stage III patients. Conclusion Supplementation with omega-3 fatty acids improved nutritional status and reduced chronic inflammatory responses in patients with stage II-III non-small cell lung cancer undergoing postoperative chemotherapy.This randomized clinical trial was registered at AEARCT (AEARCTR-0007165) on 11 February 2021.